Effects of an elliptically polarizing undulator on the beam dynamics in PLS-II - S. Shin (2018)
© 2016, The Korean Physical Society. The non-linear effects caused by the intrinsic field’s transverse roll-off in an elliptically polarizing undulator with a 72-mm period and a maximum peak field of 0.72 T (EPU72) on the dynamics aperture of the Pohang Light Source II (PLS-II) were investigated. A kick-map and a frequency map analysis both demonstrated that EPU72 will not reduce the lifetime or cause injection problems in PLS-II.